Farmers’ Evaluation of Inpari IR Nutrizinc Biofortified Rice Attributes in Jember Regency - Yunita Prasetyo Ningrum; Luh Putu Suciati; Ahmad Zainuddin; Intan Kartika Setyawati (Citakonsultindo, 2026)
Rice yields are influenced by seed varieties and biofortification. In 2019, the Indonesian government launched Inpari IR Nutrizinc rice to increase productivity and health benefits. This variety supports the government’s program to combat stunting in Jember Regency, one of the regencies with high stunting rates. This study aims to evaluate the seed performance and farmer satisfaction with Inpari IR Nutrizinc rice in Jember Regency, with a focus on farmers’ attitudes. The study was conducted in the villages of Mumbulsari, Ajung, Kebon Agung, and Gugut in Jember Regency using quantitative descriptive methods and the Fishbein multi-attribute approach. The study involved 40 farmers who were members of farmer groups that received Inpari IR Nutrizinc seeds in 2022. These attributes included productivity, resistance to pests and diseases, fertilizer use, harvest time, seed viability, seed quality, tolerance to water stress, plant drought, pesticide/insecticide use, ease of marketing unhusked rice, access to seeds and the selling price of unhusked rice, and the purchase price of Nutrizinc seeds. The research results show that farmers’ attitude toward Inpari IR Nutrizinc rice was rated at 195.5, indicating a neutral attitude. The highest-rated attribute among farmers was seed quality, while the lowest-rated attribute was the ease of marketing paddy.